2015
DOI: 10.12968/hmed.2015.76.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Panton-Valentine leukocidin osteomyelitis in children: a growing threat

Abstract: Panton-Valentine leukocidin-producing Staphylococcus aureus osteomyelitis is associated with multiple complications including multiple abscesses, deep vein thrombosis and fulminant sepsis. This article reviews the literature concerning this emerging threat which is currently under-recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…It was found that people living in closed communities with close contact (prisons and military training camps) and those who participate in contact sports (gym, rugby, wrestling and judo) are at risk. In addition, poor personal hygiene and use of contaminated shared items, such as towels, can increase the risk of infection 2. Cutaneous infections are often recurrent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that people living in closed communities with close contact (prisons and military training camps) and those who participate in contact sports (gym, rugby, wrestling and judo) are at risk. In addition, poor personal hygiene and use of contaminated shared items, such as towels, can increase the risk of infection 2. Cutaneous infections are often recurrent.…”
Section: Discussionmentioning
confidence: 99%
“…PVL-MSSA can cause septic shock and could be fatal 9. It is also associated with osteomyelitis, septic arthritis and pyomyositis 2. A systematic review of 32 patients demonstrated that septic shock, influenza like prodrome and absence of previous skin and soft tissue infections are associated with fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of PVL-producing strains does not exceed 2-5% among human routine clinical isolates in Europe, but can be higher in some other countries [111]. Associations with osteomyelitis and pyomyositis are now strongly suggested [117][118][119][120][121][122][123]. The locus encoding PVL is inside related bacteriophages [124][125][126][127]128].…”
Section: Panton-valentine Leukocidin (Pvl)mentioning
confidence: 99%